2010
DOI: 10.1073/pnas.1014051107
|View full text |Cite
|
Sign up to set email alerts
|

Slc15a4, AP-3, and Hermansky-Pudlak syndrome proteins are required for Toll-like receptor signaling in plasmacytoid dendritic cells

Abstract: Despite their low frequency, plasmacytoid dendritic cells (pDCs) produce most of the type I IFN that is detectable in the blood following viral infection. The endosomal Toll-like receptors (TLRs) TLR7 and TLR9 are required for pDCs, as well as other cell types, to sense viral nucleic acids, but the mechanism by which signaling through these shared receptors results in the prodigious production of type I IFN by pDCs is not understood. We designed a genetic screen to identify proteins required for the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
220
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(234 citation statements)
references
References 45 publications
14
220
0
Order By: Relevance
“…To directly examine how pDCs contribute to systemic autoimmunity, we developed congenic C57BL/6-Fas lpr mice carrying the feeble mutation of Slc15a4. In normal background mice with this mutation, development of both pDCs and cDCs is intact, but cytokine production, particularly type I IFNs, in response to TLR7 or TLR9 ligands is absent only in pDCs (27). Accordingly, in Slc15a4 mutant C57BL/6-Fas lpr mice, pDCs were present at normal frequencies in spleen (Fig.…”
Section: Feeble Mutation Of Slc15a4 Prevents Autoimmunity In Congenicmentioning
confidence: 89%
See 2 more Smart Citations
“…To directly examine how pDCs contribute to systemic autoimmunity, we developed congenic C57BL/6-Fas lpr mice carrying the feeble mutation of Slc15a4. In normal background mice with this mutation, development of both pDCs and cDCs is intact, but cytokine production, particularly type I IFNs, in response to TLR7 or TLR9 ligands is absent only in pDCs (27). Accordingly, in Slc15a4 mutant C57BL/6-Fas lpr mice, pDCs were present at normal frequencies in spleen (Fig.…”
Section: Feeble Mutation Of Slc15a4 Prevents Autoimmunity In Congenicmentioning
confidence: 89%
“…However, IRF8 deficiency prevents us from stating a definite conclusion as to whether pDCs contribute to disease solely through hyperproduction of type I IFNs or other functions, such as antigen presentation (57). The recent identification of the mutant strain feeble, in which defective expression of the peptide/histidine transporter SLC15A4 leads to absence of endosomal TLR signaling and severely reduced production of proinflammatory cytokines, including type I IFNs, specifically in pDCs (27), has provided an experimental tool to address this question. We found that lupus-predisposed C57BL/6-Fas lpr mice carrying this mutation exhibited striking reductions in disease manifestations and extended survival, despite efficient B-cell responses to both endosomal TLR stimuli and conventional exogenous antigens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A unique membrane trafficking pathway with characteristics of endolysosomes are essential for TLR7/9 signaling and IFN production in pDCs (22,32,33). The nucleic acid-containing amyloid is retained in the early endosomes of pDCs, where the prolonged TLR9 activation can promote MyD88 signaling and subsequent IRF7 activation, which initiates the transcription of all IFN-I subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…However, TLR7 trafficking from the endolysosomes to the cell surface likely results from lysosomal exocytosis. Lysosomes specialized for secretion are known as lysosome-related organelles (LROs), where TLR7 and TLR9 are localized and deliver a signal 25,26 . AP-3 and the HermanskyPudlak syndrome proteins BLOC-1 and BLOC-2 have been shown to play a role in LRO biogenesis and TLR7/9 responses 25,26 .…”
Section: Discussionmentioning
confidence: 99%